Effect of manual physical therapy on sleep quality and jaw mobility in patients with bruxism: A biopsychosocial randomized controlled trial - El-Gendy, Mohamed H.; Ibrahim, Mostafa M.; Helmy, Emad S.; Neamat Allah, Neama H.; Alkhamis, Batool Abdulelah; Koura, Ghada M.; Hamada, Hamada A. (Frontiers in Neurology, 2022)
This study aimed to investigate the effects of deep-stripping and trigger-point pressure release massage on the Pittsburgh Sleep Quality Index (PSQI), jaw mobility, and pressure pain threshold (PPT) of masticatory muscles in patients with sleep bruxism. A randomized controlled trial was conducted among 45 patients diagnosed with sleep bruxism. The patients were randomly assigned to three groups. Group I was the control group and included five men and 10 women; Group II was the deep-stripping massage group, which included two men and 13 women; and Group III was the pressure release group, which involved four men and 11 women. Patients were tested two times, before and after 6 weeks. Group I received transcutaneous electrical nerve stimulation and passive stretching; Group II received a deep-stripping massage; and Group III received a trigger-point pressure release massage. Findings revealed significant improvements in PSQI (p = 0.0001), jaw opening (p = 0.0001), jaw protrusion (p = 0.0001), jaw left lateral movement (p = 0.004), jaw retraction (p = 0.0001), right temporalis PPT (p = 0.0001), left temporalis PPT (p = 0.0001), right master PPT (p = 0.001), left master PPT (p = 0.001), right lateral pterygoid PPT (p = 0.001), left lateral pterygoid PPT (p = 0.001), right digastric muscle PPT (p = 0.001), and left digastric muscle PPT (p = 0.001) in the post-test condition in Group II compared with Group I and Group III. Deep-stripping massage improved PSQI, jaw mobility, or PPT of the masticatory muscles compared with trigger-point pressure release massage and traditional treatment techniques in patients with sleep bruxism.